The Effect of Kangaroo Mother Care After Duodenal Obstruction in Neonates - Zhu, Li-Bo; Xu, Yan-Hua; Li, Jin-Fen; Hu, Xue; Lu, Chun-Yan; Li, Rui-Lan; Shi, Cai-Ping; Yuan, Mei (Frontiers in Surgery, 2022)
Objective The present study aimed to explore the effectiveness of clinical application of kangaroo mother care (KMC) in neonates after surgery for duodenal obstruction in achieving total enteral nutrition (TEN) and shortening the length of hospital stay. Methods A prospective study of 60 cases of surgery for duodenal obstruction in pediatric patients in the neonatal intensive care unit of Kunming Children's Hospital between January 2018 and December 2019 was conducted. The study subjects included 15 cases with intestinal malrotation, 18 cases with circular pancreas, 10 cases with a duodenal septum, and 17 cases with duodenal atresia or duodenal stenosis. According to the single and double numbers of the operation date, the subjects were randomly divided into the control group and observation group, with 30 cases in each group. The conventional care of enhanced recovery after surgery (ERAS) was carried out in the control group, and KMC based on ERAS conventional care was implemented in the observation group. The difference in the duration to achieve TEN and the length of hospital stay between the two groups of patients after care was compared and analyzed. Results The average duration to achieve TEN for neonates with duodenal obstruction in the control group was 14.23 ± 3.17 days, while that in the observation group was 12.27 ± 1.15 days. The average length of hospital stay in the control group was 17.22 ± 4.71 days, while that in the observation group was 13.34 ± 2.70 days. There was a significant difference in the duration to achieve TEN and the average length of hospital stay between the two groups (P < 0.05). The duration to achieve TEN and the length of hospital stay in pediatric patients were significantly shorter in the observation group than in the control group. Conclusion Kangaroo mother care has important clinical significance and application value in shortening the duration to achieve TEN and the length of hospital stay in neonates after surgery for duodenal obstruction.